(untitled) (Psychology Travelogs, 2024)
The article examines responsibility as a key factor in the formation of future specialists in the process of their training. Conceptual approaches to understanding responsibility in the context of professional activity, which were considered by domestic and foreign scientists such as H. Kostyuk, S. Maksimenko, I. Beh, E. Erickson, K. Rogers, A. Maslow, V. Frankl. The structural components of responsibility, which include cognitive, emotional-motivational and behavioral aspects, are singled out. The role of moral, legal, social and personal responsibility in the professional activity of a psychologist is emphasized. In the course of empirical research, manifestations of students’ attitude to professional responsibility at various stages of education were determined. Significant differences were found between these characteristics in students of the first and fourth years. First-year students mostly have an idealized view of the profession, focusing on general moral principles, while graduates demonstrate a more conscious attitude to professional responsibility, determined by practical experience and theoretical knowledge. The results showed that graduates have higher indicators of the cognitive and regulatory components of responsibility, as well as a more developed internal locus of control, which indicates their ability to consciously make professional decisions and be responsible for their consequences. This confirmed the need to integrate issues of responsibility into the educational process. It is proposed to expand training programs for future psychologists due to the development of self-control skills, ethical thinking and reflection. The research findings emphasize the importance of professional responsibility as the main criterion of professional competence, which determines the quality of providing psychological assistance, builds trust of clients and ensures professional growth of the specialist.